(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3bUO GdCYTi GdMGQK Hf hYdI, ade jLOg, aYQL Yfg Edi ghPI Hf Ydj, Pj GdJGL, hgh ef Hfj MfajI s
(3BNQgG (B:s
(3bGd GdMSf Hf CHj GdMSf GdHUQj aj jhe aWQ, hbO QCi GdfGS hgjCJge s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ajg fbhd COHjIs
(3hbUjOI hJNejSgGs
(3hebGeI dHOjY GdReGf GdgePGfj JJYdb HPcQ GdLGMXs
(3hbUGFO hCTYGQ hQSGFd hecGJHGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs